When Basking Is Not an Option: Thermoregulation of a Viperid Snake Endemic to a Small Island in the South Atlantic of Brazil - Bovo, Rafael P. [UNESP]; Marques, Otavio A. V.; Andrade, Denis V. (Amer Soc Ichthyologists & Herpetologists, 2012)
It is broadly accepted that snakes are able to regulate their body temperature (T-b) behaviorally, but fundamental differences in this ability have been suggested to exist between temperate and tropical species. Herein, we examined the thermal ecology of the Golden Lancehead, Bothrops Insular's, a critically endangered Neotropical crotaline snake endemic to Queimada Grande Island (QGI), southeastern Brazil. We sampled T-b's of individual snakes found in the field and tested which proximal factors, biotic and abiotic, were potentially relevant for their thermoregulatory behavior and T-b selection. We verified whether T-b regulation would be compensated, through the day and/or seasons, by adjustments in the thermoregulatory effort. Finally, we hypothesized that for a Neotropical snake, the thermoregulatory effort would be lower because the thermal quality of habitat is higher compared to species inhabiting temperate zones. In general, B. insularis conformed to this hypothesis. However, seasonal declines in the thermal quality of habitat during the colder seasons and during nighttime were compensated by increases in the effectiveness of thermoregulation. Overall, T-b of B. insularis is determined largely by environmental variables, particularly air temperature, with some influence of biotic factors, such as body size. Use of open areas for basking, a common thermoregulatory behavior for squamates, was largely avoided; this may be explained by ecological factors, and may be due to foraging constraints and increased risks of predation and dehydration.